Family traditions : celebrations for holidays and everyday - Berg, Elizabeth (Pleasantville, N.Y. : Reader's Digest Association, 1992)
Suggestions for today's busy families of activities and rituals that can be used to start family traditions.
Includes index.
Adult
Adult
Keywords: Family festivals; Holidays; Family life; Festivals; Holidays